Pengaruh Brand Image, Promosi dan Harga Terhadap Keputusan Penggunaan Aplikasi Grabfood di Surabaya - Sabita Tiarailsa; Rusdi Hidayat N; Yanda Bara Kusuma; Budi Prabowo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this study is to analyze brand image, promotion, and price simultaneously with the reasons for using the GrabFood application in Surabaya, to analyze brand image and promotion separately with the reasons for using the GrabFood application in Surabaya, to analyze prices and prices separately for reasons of use. applications, and to analyze brand image and promotion simultaneously by using the application. The type of analysis used is quantitative analysis with the help of the SPSS 23 package for Windows. Each GrabFood application user in Surabaya is the sample population in this survey, and there are around 150 respondents. The type of data used is the source of the respondents. The data collection method used a Google Form questionnaire. The result of this study indicate that Brand Image, Promotion, and Price are positively and significantly correlated with the desire of Surabaya residents to use the GrabFood application.